PERUBAHAN TRADISI DO’A PADANG DI KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Dona Yulita; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The first aim of this study to find out how the process of implementation of Padang Prayer tradition for villagers Muaro Sentajo. Second, to know the what the stages are experiencing a change in the implementation of Prayer tradition Padang. three factors that influence the occurrence of the change. To analyze the data that has been in perolah of this research used descriptive analysis with images of the phenomena that exist in the field and then interpret them according to the methods, theories, techniques, and those of the author with a repertoire of existing literature. This research was conducted in the village of the District Sentajo Muaro Sentajo Kingdom Regency Kuantan Singingi. The results of research in the field shows that there are several stages in the implementation of this desert tradition of prayer: first, the stage prior to implementation, making seedlings and meetings, which in this meeting to discuss among other things the implementation time, Specifies the number of contributions, the formation of the committee, to determine who will The legislation, the second phase of implementation make traditional, mutual cooperation, cut buffalo, cooked on site. In the implementation of this tradition Padang Prayer has been a change in several stages, among others, mutual cooperation, cut buffalo, invitations, cooking on site, art. to keep the public need for the preservation of traditional wisdom that is considered a sacred in society terutaman for rice farming. a tradition that is still inherent in the community is a tradition that should Prayer Padang socialized back to the next generation where tradition is increasingly changing and not merely an entertainment alone.Key words: Tradition, Change, Agriculture